Unmet need for contraception and its associated factors among adolescent and young women in Guinea: A multilevel analysis of the 2018 Demographic and Health Surveys - Sidibé, Sidikiba; Grovogui, Fassou Mathias; Kourouma, Karifa; Kolié, Delphin; Camara, Bienvenu Salim; Delamou, Alexandre; Kouanda, Seni (Frontiers in Global Women's Health, 2022)
Despite the recent repositioning efforts to increase the use of modern contraceptives, the prevalence of unmet need for contraception remains high among adolescent and young women in Guinea. This study analyzed the individual and contextual factors associated with the unmet need for contraception among adolescent and young women in 2018 in Guinea. We conducted a secondary analysis of the 2018 Demographic and Health Survey data. Multilevel mixed-effects logistic regression models were used to assess the association between individual and contextual characteristics and unmet need for contraception among adolescents and young women. Adjusted odds ratios (AORs) with their 95% confidence intervals (CIs) were calculated, with statistical significance set at p < 0.05. The prevalence of total unmet need for contraception was 22.6% (95% CI, 18.1–27.8). Being an adolescent aged 15–19 years (AOR = 1.44; 95% CI, 1.01–2.05), unmarried (AOR = 5.19; 95% CI, 3.51–7.67), having one or two children (AOR = 3.04; 95% CI, 2.18–4.25), or more than two children (AOR = 4.79; 95% CI, 3.00–7.62) were individual factors associated with the unmet need for contraception. As for community factors, only living in Labé (AOR = 2.54; 95% CI, 1.24–5.18) or Mamou (AOR = 1.73; 95% CI, 1.21–2.48) was significantly associated with the unmet need for contraception. In conclusion, both individual and community characteristics were significantly associated with the unmet need for contraception. This highlights the need to focus and strengthen communication and counseling strategies targeting adolescents and young women and aiming to increase the uptake of family planning in Guinea.